Migration ranks for bowhead whales (Balaena mysticetus) at Barrow in spring - Sadykova , Dinara; Schweder , Tore (J. Cetacean Res. Manage., 2023)
In a series of aerial photographic surveys of bowhead whales migrating past Barrow in Alaska in the spring, 40 individuals were captured in more than one year. To study individual-specific persistency in migratory pattern, the relative ranks of the captures of these whales among all captures that year were analysed. Controlling for body length and the presence of calves, the correlation of relative ranks in individuals captured multiple times was found not to be significantly different from zero (p-value=0.78).